2014
DOI: 10.1136/bmjopen-2014-005608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of My Medication Passport: a patient-completedaide-memoiredesigned by patients, for patients, to help towards medicines optimisation

Abstract: ObjectivesA passport-sized booklet, designed by patients for patients to record details about their medicines, has been developed as part of a wider project focusing on improving prescribing in the elderly (‘ImPE’). We undertook an evaluation of ‘My Medication Passport’ to gain an understanding of its value to patients and how it may be used in communications about medicines.SettingThe Passport was launched in secondary care with the initial users being older people discharged home after an admission to one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 7 publications
7
42
0
1
Order By: Relevance
“…2 Diabetes and asthma are two long-term conditions where such a passport might help encourage young patients in supporting self-care. 4 We believe that MMP can make an important contribution to the management of medicines for children, young people, and their parents and carers. MMP may be one method to offer parents and carers an opportunity to be more empowered in discussing medication-related issues with clinicians across care settings.…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…2 Diabetes and asthma are two long-term conditions where such a passport might help encourage young patients in supporting self-care. 4 We believe that MMP can make an important contribution to the management of medicines for children, young people, and their parents and carers. MMP may be one method to offer parents and carers an opportunity to be more empowered in discussing medication-related issues with clinicians across care settings.…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…The paper passport solution is designed to be small and convenient to carry (the size of a credit card) and can provide medical professionals the medical data needed to treat the patient immediately [13]. Another example of these paper-based passports can be seen in the research carried out by Barber et al [14]. This passport was developed as a medication aid and allowed geriatric patients to record and review their medications and dosages.…”
Section: Patient Passports Definition and Reviewmentioning
confidence: 99%
“…An evaluation of MMP use demonstrated that it worked well as an aide‐memoire and to improve communication between patients, carers, doctors, pharmacists and other health‐care professionals. Subsequently, MMP was used by other types of user …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, MMP was used by other types of user. 27,28 In 2013, the MMP innovation was launched outside the initial to work as part of a service improvement team. This can be seen as part of a larger picture in which a policy context had supported greater attention being paid to enhancing patient involvement in health service improvement.…”
Section: Introductionmentioning
confidence: 99%